2012
DOI: 10.5171/2012.747338
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits: Business versus Technical Graduates

Abstract: Effective interactions depend largely on personality traits, which is a consistent and longlasting tendency in behavior. In psychology, five major trait factors (Big Five personality traits) have been generally used to assess personality of people. The study highlights the practicality of importance-performance analysis as a means to assessing the importance of personality traits dimension that should be possessed by Malaysian graduates. The importanceperformance analysis is used to evaluate the gap in persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Individuals who are high on agreeableness are considerate, easy-going, good-natured, adaptive, cooperate with others and help others create and sustain existing relationships (Sung and Choi, 2009;Migliore, 2011;Ranwala and Dissanayake, 2016), as opposed to less agreeable individuals who are deceitful, self-centered, and suspicious. With regards to employment, individuals with an agreeableness personality preference usually seek supportive environments and are usually courteous, trustworthy, flexible and good-natured (Abidin and Daud, 2012). Perkins (2016) found that agreeableness plays a vital role in the non-contracted aspects of performance as individuals with this personality trait have the tendency to do their jobs without being ordered to do so and also corporate with co-workers and help them do their jobs and thus are viewed as model employees in the workplace.…”
Section: Self-perceived Employabilitymentioning
confidence: 99%
“…Individuals who are high on agreeableness are considerate, easy-going, good-natured, adaptive, cooperate with others and help others create and sustain existing relationships (Sung and Choi, 2009;Migliore, 2011;Ranwala and Dissanayake, 2016), as opposed to less agreeable individuals who are deceitful, self-centered, and suspicious. With regards to employment, individuals with an agreeableness personality preference usually seek supportive environments and are usually courteous, trustworthy, flexible and good-natured (Abidin and Daud, 2012). Perkins (2016) found that agreeableness plays a vital role in the non-contracted aspects of performance as individuals with this personality trait have the tendency to do their jobs without being ordered to do so and also corporate with co-workers and help them do their jobs and thus are viewed as model employees in the workplace.…”
Section: Self-perceived Employabilitymentioning
confidence: 99%
“…George et al argue that strong engagement and an ability to demonstrate initiative and entrepreneurship are important in extrovert's work roles. High levels of Extroversion are typical in business occupations (Lounsbury et al, 2009) and are a prerequisite to business success (De Janasz et al, 2002), although Abidin and Daud (2012) argue that it is still lacking in business graduates in relation to industry requirements. Agreeableness concerns individual orientations to interpersonal relationships (Graziano and Tobin, 2009), described by Poropat (2009) as 'likability and friendliness' (ibid, p 322), and is characterized by 'forgiving attitudes, belief in cooperation, inoffensive language, reputation as a pushover ' (McCrae and Costa, 1999, p. 164), using terms such as 'appreciative, forgiving, generous, sympathetic, kind, warm, trusting' (McCrae and John, 1992, p 178).…”
Section: Personality Traits Definedmentioning
confidence: 99%
“…Relatively high levels of Extroversion in business graduates predict efficiency (Abidin and Daud, 2012) and strong job performance, particularly for those jobs involving social interaction such as management and sales (Barrick and Mount, 1991). The relatively high Emotional Stability is critical for managing the stress and pressure associated with the corporate world (Lounsbury et al, 2009), an ability deemed highly important by graduate employers (Casner-Lotto and Barrington, 2006;FSSC, 2007).…”
Section: Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Ramli, Latifah and Ng (2008) used IPA to assess the improvements in delivering its services to students at an Open University in Malaysia whilst Abidin and Daud (2012) used the IPA to compare the personality traits of business and technical graduates. In another study, Abdul Hamid, Islam, and Abd Manaf (2014) investigated graduates' employability skills as perceived by employers.…”
Section: Importance-performance Analysis (Ipa)mentioning
confidence: 99%